Adsorption and desorption kinetics for diffusion controlled systems with a strongly concentration dependent diffusivity - Ruthven, Douglas M. (Diffusion Fundamentals, 2007)
The formal solution to the diffusion equation for transient adsorption in a semiinfinite medium with a strongly concentration dependent diffusivity, originally derived by Fujita ( 3 ), has been extended to desorption. Profiles for adsorption and desorption are compared and simplified asymptotic expressions which are useful when the diffusivity ratio is large are derived. The effect of a strongly concentration dependent diffusivity on adsorption and desorption kinetics is briefly considered.